2014
DOI: 10.1038/srep03993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imprint of Exposure to Naturally Occurring Genetic Variants of Human Cytomegalovirus on the T cell Repertoire

Abstract: Exposure to naturally occurring variants of herpesviruses in clinical settings can have a dramatic impact on anti-viral immunity. Here we have evaluated the molecular imprint of variant peptide-MHC complexes on the T-cell repertoire during human cytomegalovirus (CMV) infection and demonstrate that primary co-infection with genetic variants of CMV was coincident with development of strain-specific T-cell immunity followed by emergence of cross-reactive virus-specific T-cells. Cross-reactive CMV-specific T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Primary coinfection with genetic variants of CMV is coincident with development of strain-specific T cell immunity followed by the emergence of cross-reactive virus-specific T cells (75). Crossreactive CMV-specific T cells exhibit a highly conserved public T cell repertoire, whereas T cells directed toward specific genetic variants display oligoclonal repertoires unique to each specimen (75). Such diversity in immune response would also be expected to affect cross-reactive immune effects on allografts.…”
Section: Viral Genetics and Variability In Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Primary coinfection with genetic variants of CMV is coincident with development of strain-specific T cell immunity followed by the emergence of cross-reactive virus-specific T cells (75). Crossreactive CMV-specific T cells exhibit a highly conserved public T cell repertoire, whereas T cells directed toward specific genetic variants display oligoclonal repertoires unique to each specimen (75). Such diversity in immune response would also be expected to affect cross-reactive immune effects on allografts.…”
Section: Viral Genetics and Variability In Immune Responsementioning
confidence: 99%
“…One strain (JP) sequenced from a clinical specimen contained two mutations including one for viral IL-10, an immune-evasion function, implying that HCMV immune evasion mutants exist in human infections (74). Primary coinfection with genetic variants of CMV is coincident with development of strain-specific T cell immunity followed by the emergence of cross-reactive virus-specific T cells (75). Crossreactive CMV-specific T cells exhibit a highly conserved public T cell repertoire, whereas T cells directed toward specific genetic variants display oligoclonal repertoires unique to each specimen (75).…”
Section: Viral Genetics and Variability In Immune Responsementioning
confidence: 99%
“…In addition, new strategies have been developed for concurrent characterization of the CDR3 sequences of TCR ␣ and ␤ chains in epitope-specific CD8 ϩ T cells through simultaneous amplification of CDR3␣ and CDR3␤ transcripts from single cells (12)(13)(14). Because CDR3 loops interact specifically with the MHC-bound antigenic peptide (15), CDR3 sequences serve as unique markers for clonal expansion after T cell activation.…”
Section: Human Cytomegalovirus (Cmv)mentioning
confidence: 99%
“…It has also been demonstrated that SOT recipients show an increased duration of viremia following reactivation of multiple genotypic isolates (12), suggesting potentially reduced immunological control following coinfection. Despite these observations, and considering the critical role T cell immunity plays in the control of CMV, very little research has been performed that specifically examines the impact of genetically distinct variants of CMV on CMV-specific T cell immunity (13)(14)(15). While this is particularly relevant for R ϩ /D Ϫ HSCT patients, who are at increased risk of CMV-associated complications, immune control of CMV infection in R ϩ /D ϩ recipients could also be impacted by exposure to distinct genetic viral variants of the recipient that are not efficiently controlled by preexisting donor immunity.…”
mentioning
confidence: 99%
“…While this is particularly relevant for R ϩ /D Ϫ HSCT patients, who are at increased risk of CMV-associated complications, immune control of CMV infection in R ϩ /D ϩ recipients could also be impacted by exposure to distinct genetic viral variants of the recipient that are not efficiently controlled by preexisting donor immunity. To address the impact genetic variation has upon T cell immunity, we focused upon the immunodominant immediate early 1 gene (IE-1) of CMV, which has previously been shown to encode significant genetic variation, including within immunodominant CD8 ϩ T cell epitopes (13)(14)(15). Using pyrosequencing analysis to identify genetic variation within IE-1, and IE-1-encoded epitopespecific T cell analysis, we sought to determine the impact of genetic variation and exposure to multiple viral variants on the induction of CMV-specific T cell immunity in a cohort of HSCT recipients.…”
mentioning
confidence: 99%